The phonoaudiologist in the health sector (Colombia Medica, 1990)
This article discusses, in general, the present situation of the speech therapist within the health worker. It attempts to justify the presence of the speech therapist at the primary health care level, which enables him (her) to be a protagonist in preventing communication disorders.